Sutureless technique combined with vertical vein incision and pulmonary veins unroofed for correction of infracardiac total anomalous pulmonary venous connection - Bing, Zhen; Chen, Rui; Xing, Quansheng; Xing, Pengchao; Lv, Bei (Frontiers in Pediatrics, 2023)
Objective: We report the surgical method which is sutureless technique combined with vertical vein incision and pulmonary veins unroofed(semi-sutureless technique) to correct infracardiac total anomalous pulmonary venous connection.The clinical characteristics of 21 patients, who were diagnosed with infracardiac total anomalous pulmonary venous connection from February 2017 to March 2022, were analyzed retrospectively. They were divided into three groups according to different surgical methods. (1) Conventional surgery group: 5 cases, the median age of 16 days (interquartile range, 9-27 days), the median weight of 3.25 kg (interquartile range, 3.1-3.42kg). There were no preoperative pulmonary vein obstruction, preoperative ventilator support, and emergency surgery. (2) Sutureless technique group: 7 cases, the median age of 12 days (interquartile range, 5-16 days), the median weight of 3.04 kg (interquartile range, 2.76-3.20kg). There were 2 cases of preoperative pulmonary vein obstruction, 4 cases of preoperative ventilator support, and 7 cases of emergency operation. (3) semi-Sutureless technique group: 9 cases, the median age of 14 days (interquartile range, 7-24 days), the median weight of 3.22 kg (interquartile range, 3.15-3.50kg). There were 4 cases of preoperative pulmonary vein obstruction, 2 cases of preoperative ventilator support, and 7 cases of emergency operation.Results: Conventional surgery group: 1 case of postoperative low cardiac output syndrome, 2 cases of postoperative supraventricular tachycardia, no postoperative death, and 1 case of pulmonary vein obstruction. Sutureless technique group: 2 cases of postoperative low cardiac output syndrome, 1 case of postoperative supraventricular tachycardia, no postoperative death, and 1 case of postoperative pulmonary vein obstruction. semi-Sutureless technique group: 3 cases had low cardiac output syndrome and 2 cases had supraventricular tachycardia after the operation. 1 case died early after the operation, who had been admitted to the hospital after cardiopulmonary resuscitation in the emergency room. There was no death or pulmonary vein obstruction after the operation.semi-Sutureless technique has positive effects. This surgery method can enlarge the anastomotic stoma, increase the volume of the left atrium, reduce the tension of the anastomotic stoma, fix the pulmonary vein to avoid distortion, and prevent postoperative hemorrhage.